Association between abdominal obesity and diabetes in India: Findings from a nationally representative study - Rajat Das Gupta; Rohan Jay Kothadia; Ateeb Ahmad Parray (Diabetes Epidemiology and Management, 2023)
Background: Both abdominal obesity and diabetes are two major public health problems in India. This study aimed to find out the association between abdominal obesity and diabetes in Indian adult population using nationally representative National Family Health Survey 2019–21 data. Methods: Diabetes was defined as having a raised blood glucose level or seeking treatment for diabetes. Abdominal obesity was defined as a waist-hip ratio of >0.90 for males and >0.85 for females. After adjusting for covariates (including body mass index), multivariable logistic regression was carried out to identify the association between abdominal obesity and diabetes. Findings: In total, 687,607 samples were included. The prevalence of diabetes was 8.65% and 7.39% among male and female participants, respectively. The prevalence of abdominal obesity was 51.77% and 57.91% among male and female, respectively. In both gender, abdominal obesity was associated with diabetes. Among the male and female, the odds of having diabetes 27% (AOR:1.27; 95% CI: 1.13–1.42) and 5% (AOR: 1.05; 95% CI: 1.00–1.11) higher among those who had abdominal obesity than those who did not have abdominal obesity. A significant interaction was observed between abdominal obesity and high body mass index (overweight and obesity) regarding the odds of diabetes. Conclusion: Abdominal obesity was significantly associated with diabetes in Indian population. The high burden of abdominal obesity should be addressed to prevent diabetes.